A Window on the Study of Aversive Instrumental Learning: Strains, Performance, Neuroendocrine, and Immunologic Systems - de Oliveira, Caroline C.; Gouveia, Flávia V.; de Castro, Marina C.; Kuroki, Mayra A.; dos Santos, Lennon C. T.; Fonoff, Erich T.; Teixeira, Manoel J.; Otoch, José P.; Martinez, Raquel C. R. (Frontiers in Behavioral Neuroscience, 2016)
The avoidance response is present in pathological anxiety and interferes with normal daily functions. The aim of this article is to shed light on performance markers of active avoidance (AA) using two different rat strains, Sprague-Dawley (SD) and Wistar. Specifically, good and poor performers were evaluated regarding anxiety traits exhibited in the elevated plus maze (EPM) and corticosterone levels and motor activity in the open field test. In addition, the plasma levels of Interleukin-6 (IL-6), Interleukin-1Beta (IL-1beta), Nerve Growth Factor Beta (NGF-beta), Tumor Necrosis Factor-Alpha (TNF-alpha) and cytokine-induced neutrophil chemoattractant 1 (CINC-1) were compared in the good and poor performers to better understand the role of the immunologic system in aversive learning. Behavioral criteria were employed to identify subpopulations of SD and Wistar rats based on their behavioral scores during a two-way AA test. The animals were tested for anxiety-like behavior in the EPM and motor activity in the open-field test. Plasma corticosterone levels were measured at the end of the avoidance test. Cytokine levels of IL-6, IL-1beta, NGF-beta, TNF-alpha and CINC-1 were measured in the plasma of the Wistar rats. Sixty-six percent of the Wistar rats and 35% of the SD rats exhibited a poor performance. This feature was associated with a decrease in anxiety-like behavior in the EPM. The poor and good performers exhibited lower levels of corticosterone compared with the control animals, which suggests that training alters corticosterone levels, thereby leading to hypocortisolism, independent of the performance. The CINC-1 levels were increased in the poor performers, which reinforces the role of immunologic system activation in learning deficits. Our study provides a better understanding of the complex interactions that underlie neuroimmune consequences and their implications for performance.